Are institutional investors with multiple blockholdings effective monitors? - Kang, Jun-Koo (2019)
We examine whether institutions’ monitoring effectiveness is related to the number of their blockholdings. We find that the number of blocks that a firm's large institutions hold is positively associated with forced chief executive officer (CEO) turnover-performance sensitivity, abnormal returns around forced CEO turnover announcements and 13D filings, and changes in firm value. These results are particularly evident when institutions have multiple blockholdings in the same industry, when they have activism experience, or when they have long-term blockholdings in their portfolio firms. Our results suggest that information advantages and governance experience obtained from multiple blockholdings are important channels through which institutions perform effective monitoring.